Work, psychiatry and society, c. 1750-2015 - Ernst, Waltraud, 1955- (Book collections on Project MUSE., 2017)
This book offers the first systematic critical appraisal of the uses of work and work therapy in psychiatric institutions across the globe, from the late eighteenth to the end of the twentieth century. Contributors explore the daily routine in psychiatric institutions and ask whether work was therapy, part of a regime of punishment or a means of exploiting free labour. By focusing on mental patients' day-to-day life in closed institutions, the authors fill a gap in the history of psychiatric regimes. The geographical scope is wide, ranging from Northern America to Japan, India and Western as well as Eastern Europe, and the authors engage with broad historical questions, such as the impact of colonialism and communism and the effect of the World Wars. The book presents an alternative history of the emergence of occupational therapy and will be of interest not only to academics in the fields of history and sociology but also to health professionals.